Stabilnost naselbinskega prostora - Fikfak, Alenka (AR. Arhitektura, raziskave, 2005)
Characteristics of settlements patterns and forms are encompassed between stability and instability. We evaluate them according to their historical value, but their image, as perceived today after centuries of changing, adapting and transformation, cannot be recognised in its original form. Time is the "super-factor" that balances, determines and transforms internal forces of settlement structures, and is decisively conditioned by social links. Instability can change to stability and vice versa. Individual elements of the pattern constantly change, independently from the comprehensive system (expansion and shrinking of settlements and their particular residential units), but we cannot predict the moment when the system becomes unstable and vice versa. Thus the patterns superficial character and ratio between the level of particularisation or dispersion constantly adapt to new circumstances. The development of various forms of settlement space was conditioned by morphological-geographical features of the area, production (management method), as well as the history of agriculture and colonisation. The first changes in the countryside emerged with the introduction of new transport links. In Slovenia the most substantial change happened after WW2, mainly following changes in organisation in the social-political system and introduction of numerous measures implying collectivisation (nationalisation) in the countryside.
Keywords: naselbine; naselbinski prostor; naselbinski vzorci; podeželje; rural area; naselbinske strukture; stabilnost; Slovenia; Slovenija